Genetic diversity analysis among Capsicum annuum mutants based on morpho-physiological and yield traits - Karim, K. M. Rezaul; Rafii, Mohd Y.; Misran, Azizah; Ismail, Mohd Firdaus; Harun, Abdul Rahim; Ridzuan, Raihana; Chowdhury, Mst. Farhana Nazneen; Hosen, Monir; Yusuff, Oladosu; Haque, Md Azadul (Multidisciplinary Digital Publishing Institute, 2022)
It is crucial to assess genetically superior parents when developing novel hybrids. This experiment was conducted to find out the diversity of 27 Capsicum annuum mutant lines derived from two varieties.To achieve the objective, 23 morpho-physiological and yield traits were recorded through two planting seasons. Highly significant differences (p < 0.01) were recorded among the studied traits. There was a strong to moderately positive phenotypic association between yield and all other morphological traits except first bifurcation length, stem diameter, pedicle length, flowering date, and maturity date. A higher Genotypic Coefficient of Variation (GCV) and Phenotypic Coefficient of Variation (PCV), combined with moderate to high heritability and high hereditary progress, have been found in the number of fruits per plant, fruit yield per plant, and number of seeds per fruit. High heritability was found in yield characteristics, vis-à-visnumber of seeds per fruit, number of fruits per plant, and indicated high genetic advance. The studied genotypes were divided into six groups after the cluster analysis. Based on the correlation matrix of 23 quantitative characteristics, principal component analysis revealed that the percentage of variation for PC1 and PC2 is 28%and 19%, respectively, andPC1 represents the largest percentage of the overall total variation. The calculated genetic distance also explains the potential of heterosis breeding. The revealed findings might be helpful for breeders to target quantitative characters and the parental lines of C. annuum during the execution of their future breeding programmes for developing high-yielding and climate-resilient chilli varieties.